Preterm birth screening, prevention and management: a cross-sectional online survey of practice in the Oxford Academic Health Science Network (The AHSN Network) - Muriithi, F (2018)
Background: A survey in the six hospitals of the Oxford Academic Health Science Network (The AHSN Network) with the aim of establishing current practice for screening, prevention and management of preterm labour and assessing variation in practice.